Interaction between bacteriophages, Xanthomonas campestris pv. malvacearum and Gossypium hirsutum - and R.P. SINGH, J.P. VERMA, G.N. DAKE (Indian Phytopathology, 2002)
Cotton seedlings absorbed phages within 3 hours after root immersion in a phage lysate of X:c. pv. malvacearum (Xcm) containing 5 x 10 7 pfu/m!. The phages could be detected in cotyledons within 12 hours. The longevity of phages (in absence of X.Â«. pv.malvacearum) in cotton seedlings was 48 h in root dip method; while in leaves the phages could be detected for 24 h in spray inoculation and 48 h in leaf infiltration by syringe. Pre-inoculation of phage at 1 h afforded maximum protection for both SR (40% protection) and HR (80% protection) of Xcm respectively on Acala-44 (susceptible, SR) and 101-102-B (resistant, HR). However, effective protection was achieved only at massive doses of phage (phage: Xcm ratio was 30 : 1). The seeds treated with phage lysate showed 95 per cent reduction in cotyledonary infection. Phages reduced Xcm population to levels insufficient to induce symptoms. Repeated application of phage lysate was considered necessary for successful biological control, however, more work is needed before bacteriophages can be used in management of blight of cotton .